Nutritional status and the possible related factors among children younger than two years - Eman Fouad Ataia Abdelhameed; Mohamed Hasan Husein; Moshera Amin Zayed; Nafousa Ali Afifi (Cairo : Eman Fouad Ataia Abdelhameed, 2010)
According to the conceptual framework formulated by UNICEF of the causes of malnutrition nutrition intake and diseases are the direct determinant of child survival, growth and development .This study aimed at exploring some possible factors related to nutritional status of children from 6 to 24 months
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Community Medicine
Issued also as CD
Keywords: Feeding pattern; Infant and young children; Nutritional status